Creating Religious Relationality in Digital Media Platform - Dewantri, Puja (LP2M UIN Sunan Kalijaga, 2023)
Today's digital era has manifested a massive movement of people from an old society to a new society. This digital world has also changed the way people see and practise religion. Here, at least two questions are asked. First, consider how the use and accessibility of digital media affect religious knowledge and practise in order to raise religious awareness. The second question is how religion can be both a social practise and a discourse so that more people can participate in the discussion. This research aims to answer these two questions by adopting the indigenous religion paradigm which based on relationality. Indirectly, the main objective of this research is to figure out the interactions related to religious content in digital media as an up-to-date portrait of how religiosity is understood using the alternative of the religious paradigm as the embodiment of new topics in religious studies and the digital world: religious relationality paradigm. Through the three principles of the paradigm—responsibility, ethics, and reciprocity—digital media has helped to create distinctive religious awareness. [Era digital saat ini telah mewujudkan perpindahan masyarakat secara masif dari masyarakat lama ke masyarakat baru. Dunia digital ini juga telah mengubah perspektif dan praktik seseorang dalam kehidupan beragama. Karenannya, dalam artikel ini, setidaknya terdapat dua pertanyaan yang diajukan. Pertama, bagaimana penggunaan dan aksesibilitas media digital memengaruhi pengetahuan dan praktik keagamaan untuk meningkatkan kesadaran beragama. Pertanyaan kedua adalah bagaimana agama dapat menjadi praktik sosial sekaligus wacana sehingga lebih banyak orang dapat berpartisipasi dalam diskusi keagamaan. Penelitian ini bertujuan untuk menjawab kedua pertanyaan tersebut dengan mengadopsi paradigma agama lokal yang berbasis relasionalitas. Secara tidak langsung tujuan utama dari penelitian ini adalah untuk mengetahui interaksi terkait konten keagamaan dalam media digital sebagai potret terkini bagaimana religiusitas dipahami dengan menggunakan alternatif paradigma keagamaan sebagai pengejawantahan topik baru dalam kajian agama dan dunia digital: paradigma relasionalitas agama. Melalui tiga prinsip paradigma—tanggung jawab, etika, dan timbal balik—media digital telah membantu menciptakan kesadaran beragama yang khas.]